2021
DOI: 10.3389/fcvm.2021.654392
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Angiography-Derived and Wire-Based Fractional Flow Reserves in Percutaneous Coronary Intervention

Abstract: Background: Coronary angiography-derived fractional flow reserve (caFFR) measurements have shown good correlations and agreement with invasive wire-based fractional flow reserve (FFR) measurements. However, few studies have examined the diagnostic performance of caFFR measurements before and after percutaneous coronary intervention (PCI). This study sought to compare the diagnostic performance of caFFR measurements against wire-based FFR measurements in patients before and after PCI.Methods: Patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In one smaller trial with 104 patients, caFFR was compared to invasive FFR before (104 patients) and after (65 patients) PCI. The authors reported a good correlation between caFFR and FFR measurements before ( r = 0.77; p < 0.001) and after ( r = 0.82; p < 0.001) stent implantation ( 21 ). Although they reported some adverse clinical outcomes to be related to low post-procedural caFFR, the number of events and participants is too low to draw such a conclusion, which should be addressed in larger prospective trials.…”
Section: Diagnostic Performance Of Angiography-based Ffr Indicesmentioning
confidence: 94%
“…In one smaller trial with 104 patients, caFFR was compared to invasive FFR before (104 patients) and after (65 patients) PCI. The authors reported a good correlation between caFFR and FFR measurements before ( r = 0.77; p < 0.001) and after ( r = 0.82; p < 0.001) stent implantation ( 21 ). Although they reported some adverse clinical outcomes to be related to low post-procedural caFFR, the number of events and participants is too low to draw such a conclusion, which should be addressed in larger prospective trials.…”
Section: Diagnostic Performance Of Angiography-based Ffr Indicesmentioning
confidence: 94%
“…The caFFR, without using invasive pressure--wire measurement and hyperemic stimulus, overcomes these constraints and shows high diagnostic accuracy by using wire-derived FFR as the reference standard [8]. It has been confirmed that caFFR measurement is in good correlation and agreement with wire-based FFR both before and after PCI [8,[19][20][21]. Several studies proved that STEMI with multivessel disease patients can benefit from quantitative flow ratio-guided complete revascularization in the stages of acute MI [22][23][24].…”
Section: Discussionmentioning
confidence: 90%
“…Coronary Angiography-derived Fractional Flow Reserve (caFFR) is a new and practical technique to judge whether coronary artery stenosis is functional ischemia based on angiography in recent years, which can calculate the blood flow reserve fraction by using an optimized CAD algorithm without pressure guide wire and vasodilators. Compared with FFR, its accuracy and feasibility have been verified by a series of clinical trials [ [7] , [8] , [9] ]. However, it is unclear whether caFFR-guided PCI lesion selection can improve the prognosis compared with the standard angiographic guidance strategy in the real world.…”
Section: Introductionmentioning
confidence: 99%